Determinants of the use of health care services: multilevel analysis in the Metropolitan Region of Sao Paulo - Chiavegatto Filho, Alexandre Dias Porto; Wang, Yuan-Pang; Malik, Ana Maria; Takaoka, Julia; Viana, Maria Carmen; Andrade, Laura Helena (Revista de Saúde Pública, 2015)
OBJECTIVE To evaluate the individual and contextual determinants of the use of health care services in the metropolitan region of Sao Paulo. METHODS Data from the Sao Paulo Megacity study – the Brazilian version of the World Mental Health Survey multicenter study – were used. A total of 3,588 adults living in 69 neighborhoods in the metropolitan region of Sao Paulo, SP, Southeastern Brazil, including 38 municipalities and 31 neighboring districts, were selected using multistratified sampling of the non-institutionalized population. Multilevel Bayesian logistic models were adjusted to identify the individual and contextual determinants of the use of health care services in the past 12 months and presence of a regular physician for routine care. RESULTS The contextual characteristics of the place of residence (income inequality, violence, and median income) showed no significant correlation (p >; 0.05) with the use of health care services or with the presence of a regular physician for routine care. The only exception was the negative correlation between living in areas with high income inequality and presence of a regular physician (OR: 0.77; 95%CI 0.60;0.99) after controlling for individual characteristics. The study revealed a strong and consistent correlation between individual characteristics (mainly education and possession of health insurance), use of health care services, and presence of a regular physician. Presence of chronic and mental illnesses was strongly correlated with the use of health care services in the past year (regardless of the individual characteristics) but not with the presence of a regular physician. CONCLUSIONS Individual characteristics including higher education and possession of health insurance were important determinants of the use of health care services in the metropolitan area of Sao Paulo. A better understanding of these determinants is essential for the development of public policies that promote equitable use of health care services.